2023
DOI: 10.3390/su15032842
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Priority Areas for Ecological Restoration Based on Human Disturbance and Ecological Security Patterns: A Case Study of Fuzhou City, China

Abstract: The rapid increase in urbanization has brought about a great deal of ecological problems, and thus the systematic protection of the environment is vital. Ecological security patterns are important for maintaining regional ecological stability and sustainable urban development. Human disturbance is a key factor affecting the stability and sustainable development of ecosystems. This paper constructs an ecological security pattern and evaluates the degree of human disturbance in Fuzhou City. Through a comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The use of ecological sensitivity evaluation data to modify the basic resistance surface can reflect the ecological resistance status of resource-exhausted cities better than general studies [51]. Finally, the ecological source, ecological pinch point, ecological obstacle, and ecological fracture point were taken as the key areas of territorial ecological restoration, and effective ecological strategies were proposed in combination with land use types [50,78]. It was found that, unlike previous static studies, regional ecological restoration or protection activities can be better coordinated by analyzing the changes in ESP during different periods in resource-exhausted cities.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ecological sensitivity evaluation data to modify the basic resistance surface can reflect the ecological resistance status of resource-exhausted cities better than general studies [51]. Finally, the ecological source, ecological pinch point, ecological obstacle, and ecological fracture point were taken as the key areas of territorial ecological restoration, and effective ecological strategies were proposed in combination with land use types [50,78]. It was found that, unlike previous static studies, regional ecological restoration or protection activities can be better coordinated by analyzing the changes in ESP during different periods in resource-exhausted cities.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…For the construction of ecological resistance surfaces, most studies directly assigned ecological resistance values to different types of land use, a method that ignores the internal spatial heterogeneity of the same land use type [46,47]. Some scholars have used nighttime light data, ecological sensitivity assessment results, and impervious surface area to further correct the basic resistance surface on the basis of land use types [48][49][50]. The exploitation of coal resources destroys the ecological environment and exacerbates the sensitivity of regional ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the ESP cannot determine the restoration order of these protected or restored areas, nor can it determine the priority areas for implementing restoration projects. Some scholars have combined the ESP with landscape elements [32], EV [33], and human disturbance [34] to identify priority areas for ecological restoration. In particular, EV takes into account both natural factors and human activities, being more fully able to reflect the ecological situation than landscape elements and human disturbance.…”
Section: Introductionmentioning
confidence: 99%